The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1149/1.1380256
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Ti[sub n+1]AlX[sub n] (n=1-3 and X=C, N): II. Experimental Results

Abstract: In this, Part II of a two-part study, the oxidation kinetics in air of the ternary compounds Ti 2 AlC, Ti 2 AlC 0.5 N 0.5 , Ti 4 AlN 2.9, and Ti 3 AlC 2 are reported. For the first two compounds, in the 1000-1100°C temperature range and for short times ͑Ϸ20 h͒ the oxidation kinetics are parabolic. The parabolic rate constants are k x (m 2 /s) ϭ 2.68 ϫ 10 5 exp Ϫ 491.5 (kJ/mol)/RT for Ti 2 AlC, and 2.55 ϫ 10 5 exp Ϫ 458.7 (kJ/mol)/RT for Ti 2 AlC 0.5 N 0.5 . At 900°C, the kinetics are quasi-linear, and up to 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
120
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(141 citation statements)
references
References 21 publications
8
120
0
3
Order By: Relevance
“…Ti 2 AlC oxidation kinetics have been measured by various researchers [29][30][31]. Parabolic oxidation kinetics have been observed, which implies growth of the oxide scale is diffusion-controlled [26,[29][30][31].…”
Section: Diffusion Mechanism Of Microstructural Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ti 2 AlC oxidation kinetics have been measured by various researchers [29][30][31]. Parabolic oxidation kinetics have been observed, which implies growth of the oxide scale is diffusion-controlled [26,[29][30][31].…”
Section: Diffusion Mechanism Of Microstructural Evolutionmentioning
confidence: 99%
“…Parabolic oxidation kinetics have been observed, which implies growth of the oxide scale is diffusion-controlled [26,[29][30][31]. In Ti 2 AlC, the oxide scale growth is caused by inward diffusion of O 2-and outward diffusion of Al 3+ and Ti 4+ [29][30][31].…”
Section: Diffusion Mechanism Of Microstructural Evolutionmentioning
confidence: 99%
“…Oxidation resistance is one of the critical properties of MAX phases for high temperature applications [16][17][18]. Wang et al [8,19] reported that the oxidation resistance of Al 2 O 3 -forming Ti 3 AlC 2 was superior to that of SiO 2 -forming Ti 3 SiC 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The isothermal oxidation behavior of Ti 3 SiC 2 [2][3][4][5][6][7][8] and Ti 3 AlC 2 [9][10][11][12][13] has been extensively studied. The isothermal oxidation of Ti 3 SiC 2 at temperatures between 900 and 1200°C in air resulted in the formation of an outer TiO 2 layer, an intermediate SiO 2 -rich layer and an inner (TiO 2 ?…”
Section: Introductionmentioning
confidence: 99%